Overcoming barriers to fuel cell electric vehicles adoption: greener environmental governance in the Indian subcontinent - Joshi, Prasad Vasant; Sarkar, Bishal Dey; Choubey, Vardhan Mahesh; Sibai, Fadi; Jagtap, Sandeep (Elsevier, 2025)
Fuel cell electric vehicles (FCEVs) are gaining global attention as a sustainable transportation solution, yet their adoption in emerging South Asian economies remains limited. This study addresses the research gap by identifying and prioritizing barriers to FCEV adoption in India, Pakistan, and Bangladesh, regions underrepresented in existing literature. A hybrid methodology integrating Exploratory Factor Analysis (EFA), Fuzzy Set Theory (FST), and Evidential Reasoning Approach (ERA) was applied to analyze responses from 221 experts across five stakeholder groups. The results reveal that high cost, inadequate infrastructure, and lack of skilled workforce are the most critical and stable barriers. The study also proposes a scenario-based stability analysis for targeted and adaptive policy design. The study offers practical implications for policymakers and industry leaders aiming to accelerate the FCEV transition in emerging markets by providing region-specific insights.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4008 Electrical Engineering; 4017 Mechanical Engineering; 7 Affordable and Clean Energy; Energy; Fuel cell electric vehicles (FCEVs); Fuzzy evidential reasoning algorithm (FERA); Sustainability; Triple bottom line; Emerging economies